Managing land use conflicts for sustainable futures: Tourism, agriculture and mining - McKenzie, Fiona Haslam; Paul, V.; Hoath, Aileen (RWTH Aachen Univeristy, 2011)
This paper considers several mining ventures which are occurring in rural communities in Galicia, Spain and Western Australia, Australia. It compares and contrasts the communities where mining is taking precedence over other industries, examining the potential land use conflicts and the future of both the communities and the mines currently operating there. The Galician case study, Trevinca, is located 200 km inland and was once a primary producing area, notable for its scenic attributes, most particularly alpine landscapes, which have since been developed for small scale tourism purposes. Consistent with other remote, rural locations, Trevinca has an ageing demographic profile, services have been rationalised and depopulation trends have been evident for some time as young people move away to seek work elsewhere. This is despite the most lucrative local industry being slate mining. Most of the workers involved in this industry drive in and drive out (DIDO) from elsewhere and hence, many of the regional economic capital derived from slate extraction flows to other communities. The Australian case study, Boddington, by contrast, is located 100 km inland in what has traditionally been a highly productive sheep grazing area. Mining, until recently was a marginal industry in the area but due to the comparative devaluing of agriculture and the increased value of mining outputs, two mines, one extracting bauxite and the other gold and copper have increased scale and economic importance. The local population has now reversed its downward trend and there are considerable local growth pressures, particularly regarding housing. The mines workforce is a combination of DIDO and residential with the intention that the majority of workers will live locally.This paper will consider the environmental, social and economic impacts that have occurred in both the case study localities and whether strategies for the lifecycle of the mine are complimentary for the long term future of the communities supporting them. Where there have been land use conflicts, strategies for minimising the adverse outcomes will be considered.